Intrinsic dielectric properties of columbite ZnNb2O6 ceramics studied by P–V–L bond theory and Infrared spectroscopy. Issue 9 (21st March 2019) - Yang, Hongyu; Zhang, Shuren; Yang, Hongcheng; Yuan, Ying; Li, Enzhu
Abstract: In this study, intrinsic dielectric properties of ZnNb2 O6 ceramics were investigated using P–V–L chemical bond theory and far‐infrared reflectivity spectra. The largest bond ionicity and bond susceptibility of Nb–O bonds suggest that the dielectric polarizability is mainly determined by Nb–O bonds. Relative permittivity, calculated via P–V–L bond theory, is close to experimental value determined using TE011 mode. The Nb–O bonds are also crucial for the structural stability. According to far‐infrared reflectivity spectra and complex dielectric function analysis, a relatively consistent result between calculated and measured dielectric properties, fit using classical damped oscillator mode, indicate that the B1u mode at 168.87 cm −1 provides majority contribution to the dielectric properties.